(untitled) (Comprehensive Journal of Science, 2025)
This paper falls within the field of engineering technologies and focuses on developing an intelligent tool to enhance digital parental control using modern web technologies. The proposed solution, titled “Family Eye”, is implemented as a Google Chrome browser extension designed to support parents in monitoring their children’s online activities and detecting phishing websites. The extension analyzes the web pages visited by children, automatically identifying inappropriate or harmful content and logging relevant incidents, including timestamps and page details. A keylogging feature is also integrated to track typing behavior on social media platforms, without directly violating user privacy. Additionally, the system incorporates a specialized link analysis mechanism using security databases such as Google Safe Browsing and VirusTotal, allowing it to instantly alert users to potential online threats. The tool was developed using engineering techniques and web technologies including HTML, CSS, and JavaScript, within the Chrome Extensions development environment. Its features were defined based on the results of a survey conducted among parents, employees, and students, which helped tailor its functionality to real user needs. The system underwent performance testing across various environments and browsers to ensure reliability and efficiency. This paper presents an applied engineering model for a technical tool aimed at strengthening child safety on the internet and empowering parents to make informed preventive decisions. The solution offers a practical and user-friendly approach within a trustworthy technological framework